1997
DOI: 10.1002/(sici)1099-0488(199710)35:14<2195::aid-polb1>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Computer-simulation analysis of the ESR spectra of mechanoradicals in PMMA

Abstract: In this study, initially, we tried to obtain the mechanoradicals of PMMA (poly(methyl methacrylate)). For this purpose, we designed a simple drilling apparatus. Using this apparatus, we prepared some PMMA samples at 77 K in vacuum. Later, by using an ESR (electron spin resonance spectrometer), we observed ESR signals for these samples at 77 K. This means that mechanoradicals have been successfully produced by mechanical fracture in PMMA using our drilling apparatus. Secondly, we tried to identify the radicals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…In these cases, a mechanical action is usually required to generate CE, such as powerful mutual friction (rubbing) or smooth sliding between surfaces. For instance, Liu&Bard 13 induced electrons on the surface of polytetrafluoroethylene (PTFE) and poly(methyl methacrilate) (PMMA), suggesting that electrons are donated from surface states by mechanical breakage of bonds during rubbing on PMMA, which is consistent with the formation of radicals in PMMA by mechanisms earlier reported by Tatar&Kaptan 14 . Diaz et al 15 studied the polymer-polymer contact without rubbing but chemically modifying the surfaces with ion or electron donor groups.…”
Section: Introductionsupporting
confidence: 70%
“…In these cases, a mechanical action is usually required to generate CE, such as powerful mutual friction (rubbing) or smooth sliding between surfaces. For instance, Liu&Bard 13 induced electrons on the surface of polytetrafluoroethylene (PTFE) and poly(methyl methacrilate) (PMMA), suggesting that electrons are donated from surface states by mechanical breakage of bonds during rubbing on PMMA, which is consistent with the formation of radicals in PMMA by mechanisms earlier reported by Tatar&Kaptan 14 . Diaz et al 15 studied the polymer-polymer contact without rubbing but chemically modifying the surfaces with ion or electron donor groups.…”
Section: Introductionsupporting
confidence: 70%
“…It has been demonstrated that loading polystyrene21 and polycarbonate22 in tension to fracture results in releasing gaseous products consistent with bond scissions. Similar phenomena have been reported for microtoming of polyethylene23 and drilling of poly(methyl methacrylate) 24. The deformation and failure of polymers or other solids may result in the emission of ions, electrons, as well as neutral species, which is known as the phenomenon of fractoemission 25.…”
Section: Introductionsupporting
confidence: 68%
“…The spectral feature of PMMA fractured without MA (Figure 1a) remained unchanged at various stages of vibratory milling as reported in a previous paper [18], which is most characterized by five major lines with four shoulders (nine-line spectrum). It is well known that this nine-line spectrum is ascribed to a tertiary radical (single end-chain radical shown in Chart 1) [22][23][24][25][26]. On the other hand, the ESR spectra of the fractured sample of PMMA with MA at 5-min vibratory milling showed a broad singlet, and the spectral feature gradually changed with the fractured time (Figure 1b).…”
Section: Esr Spectra Observed In Mechanochemical Reaction Of Pmma and Mamentioning
confidence: 90%
“…PMMA is one of the most widely used synthetic polymers. It is also known that only the electron spin resonance (ESR) spectrum of the tertiary end-chain radical is observed at room temperature by the mechanochemical reaction of PMMA [22][23][24][25][26]. We investigated the progressive changes in ESR spectrum observed in the mechanochemical reaction of PMMA and MA together with the changes in molecular weight.…”
mentioning
confidence: 99%